2022
DOI: 10.3390/molecules27206907
|View full text |Cite
|
Sign up to set email alerts
|

Sahlep (Dactylorhiza osmanica): Phytochemical Analyses by LC-HRMS, Molecular Docking, Antioxidant Activity, and Enzyme Inhibition Profiles

Abstract: Studies have shown an inverse correlation among age-related illnesses like coronary heart disease and cancer and intake of fruit and vegetable. Given the probable health benefits of natural antioxidants from plants, research on them has increased. Dactylorhiza osmanica is consumed as a food and traditional medicine plant in some regions of Turkey, so evaluation of the biological ability of this species is important. In this study, the amount of phenolic content (LC-HRMS), antioxidant activities and enzyme inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…The reducing capacity of a compound may be a good predictor of its potential antioxidant activity. The Fe 3+ -TPTZ-reducing test was used to assess the reducing capabilities of propolis and standards [ 69 ]. In our previous study, we determined that the aqueous extract of propolis exhibited concentration-dependent (10–30 μg/mL) Fe 3+ -reducing and cupric ion (Cu 2+ )-reducing abilities with statistically significant differences ( p < 0.01) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reducing capacity of a compound may be a good predictor of its potential antioxidant activity. The Fe 3+ -TPTZ-reducing test was used to assess the reducing capabilities of propolis and standards [ 69 ]. In our previous study, we determined that the aqueous extract of propolis exhibited concentration-dependent (10–30 μg/mL) Fe 3+ -reducing and cupric ion (Cu 2+ )-reducing abilities with statistically significant differences ( p < 0.01) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because α-amylase plays a significant role in the digestion of dietary starches, its inhibition helps to prevent and control postprandial hyperglycemia. As a result, numerous studies have looked into and discovered the inhibition of α-amylase by natural products, such as plant extracts, in recent years [ 114 ]. P. granatum peel extracts in both aqueous and methanolic form were found to have no effect on the enzyme α-amylase in earlier research [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of p -hydroxybenzyl alcohol, known as neuroactive and sedative, could be also at the basis of the alleged psychoactive properties of A. pyramidalis tuber or of D. maculata flowers (see Table 1 ). The tuber of D. osmanica was used to cure coughs, inflammation, ulcers, and skin boils: Kiziltas et al [ 188 ], while investigating the tuber extract to evaluate other biological properties, found that fumaric acid, p -coumaric acid, rosmarinic acid, and vanillic acid were present. A contribution of these compounds to the beneficial effect of D. osmanica ’s tuber use cannot be excluded.…”
Section: Phytochemical Information and Pharmacology Of European Orchidsmentioning
confidence: 99%
“…Dactylorhiza osmanica : This species and its phytochemicals have been already mentioned above. Kiziltas et al [ 188 ] also found that both tuber and flowering stem extracts have anti-Alzheimer and anti-diabetes properties, as evaluated by in vitro enzymatic assays (inhibitory activity against acetylcholinesterase (AChE), α -glycosidase, and α -amylase).…”
Section: Phytochemical Information and Pharmacology Of European Orchidsmentioning
confidence: 99%